Enhancing sustainable rice production through organic plus fertilizer in irrigated paddy fields - Mulyani, Oviyanti; Sofyan, Emma Trinurani; Citraresmini, Ania; Joy, Benny; Husen, Anne Yuliana (Universitas Padjadjaran, 2025)
Sustainable rice farming is increasingly threatened by declining soil fertility, excessive reliance on chemical fertilizers, and environmental degradation from intensive agricultural practices. There is an urgent need for innovative organic fertilizer products that combine organic materials with macro and micronutrient enhancements to restore soil health effectively. This research aimed to evaluate the effect of organic plus fertilizer (OPF) as a sustainable soil amendment to improve soil nutrient status, increase paddy productivity, and enhance overall soil health. The experiment was conducted using a Randomized Block Design (RBD) with nine treatments: one recommended OPF dose, six combinations of NPK (75 – 100%) and OPF (75 – 150%), one recommended conventional NPK dose, and one control. Variables observed included plant growth, yield, and yield components, total soil nitrogen, and plant uptake of N, P, and K. Results indicated that OPF combined with NPK significantly increased plant height (29.13 – 31.38%) and number of panicles (57.89%) compared to the control. Nutrient uptake improved for nitrogen (23.68%) and potassium (15.96 – 21.28%), although no significant improvement was observed for phosphorus. Yield parameters showed an 81.97%–118.50% increase over the control. The combinations of 75% NPK + 150% OPF, 100% NPK + 75% OPF, and 100% NPK + 100% OPF produced taller plants, higher yields, greater nutrient uptake, and lower residual nitrogen in the soil. For optimal rice yield and soil health, integrated application of OPF with either a full or 75% NPK dose is recommended.